Dialektika al-Qur’an dalam al-Urf: Studi Kritis Pergeseran Makna Budaya Mappasikarawa pada Perkawinan Bugis di Era Modern - Sunuwati; Hasnani; Aris; Abdullah, Baharuddin; Darwis, Rizal (Al-Ulum, 2025)
This study examines the transformation of meaning in the Bugis society’s mappasikarawa culture, which has undergone significant shifts in values due to modernity. It employs a dialectical approach between the Qur’an and local cultural context as al-urf to map the dynamic relationship between universal Islamic values and local wisdom. Using a qualitative analytical-critical method, data was gathered through in-depth interviews, participant observation, and document analysis in Bugis regions. Findings show that mappasikarawa serves not only as a symbolic ritual but also integrates Qur’anic values sakinah, mawaddah, and rahmah. Thus, a contextual reinterpretation based on maqaṣid al-shariah and hifz al-nafs is essential to maintain its relevance and harmony with Islamic law.